Vegetation Development on Coal Waste Pile in Panyi Coal Mine - Wang, Xingming; Chu, Lei; Chu, Zhaoxia; Dong, Zhongbing (Asian Journal of Chemistry, 2013)
Exploitation and utilization of coal can result in a series of ecological environment problems. Coal waste was the solid waste released in the process of coal mining. When coal waste was dumped to form pile, it not only occupies lots of arable land, but also endangers the ecological system in coal mine district. In this study, coal waste pile of Panyi coal mine were surveyed for naturally occurring plant species and limiting factors for plant residence. The plant species, Summed dominance ratio, Species diversity index and Evenness index were calculated for the plant communities grown at the bottom of pile. Heavy metal concentrations and chemical properties in coal waste compared with uncontaminated soil were also determined. Results showed that two stable plant communities (Synodon dactylon + Setaria viridis community and Humulus scandens community) could adapt to the harsh conditions at the bottom of coal waste pile. Synodon dactylon and Humulus scandens were the dominant plants that may prove useful in future revegetation programs of coal waste pile. Elevated levels of Cd and electrical conductivity and lower levels of total P and total K might be the limiting factors affecting the residence and growth of pioneering plants.